The Importance of Family Support in Successful Treatment Adherence of Schizophrenic Patient - Lia Jessica; Izzatul Fithriyah; I Gusti Ayu Indah Ardani (Faculty of Medicine, Universitas Airlangga, 2021)
Background: Schizophrenia is a treatable disease but requires patient’s high adherence to treatment. Family support of a schizophrenic patient plays an important role in encouraging the patient to continue his treatment. This report aims to enhance the importance of family support of schizophrenic patient in patient’s adherence to achieve a good mental health for all family member.Case: A hospitalized male paranoid schizophrenic patient who was admitted and observed in Dr. Soetomo General Hospital from September 15th-25th, 2020. Patient came to the hospital with chief complaint could not stop talking (rambling) since 1 day before admission. Patient could neither eat nor sleep for that day. Patient relapsed after stopping taking medication from the psychiatrist.Discussions: The patient in this case suffered a relapse of his paranoid schizophrenia because he stopped taking medication. Lack of support from family is the most important factor in a schizophrenia patient. Psychoeducation to patient’s family about schizophrenia and the importance of medication would be a great help for patient’s adherence to treatment.Conclusions: Schizophrenia needs a long-life treatment. High adherence to treatment could improve schizophrenia’s symptoms and prevent relapse. Family support is important to make sure the patient keeps taking his medicine regularly.